ENHANCING THE COMPETITIVENESS OF MAQOM MUSIC IN THE GLOBAL CULTURAL ARENA - Masharipova Elmira Muxammedsharipovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines strategies for enhancing the competitiveness of Maqom music in the global cultural arena. It focuses on methods to increase international recognition, audience engagement, and cultural influence, while preserving the authenticity and artistic value of this unique Uzbek musical tradition. The study analyzes the role of digital platforms, branding, international festivals, cultural diplomacy, and educational initiatives in promoting Maqom globally. Emphasis is placed on integrating traditional heritage with contemporary presentation to ensure both cultural sustainability and international appeal.